Insufficient Chilling Effects Vary among Boreal Tree Species and Chilling Duration - Man, Rongzhou; Lu, Pengxin; Dang, Qing-Lai (Frontiers in Plant Science, 2017)
Insufficient chilling resulting from rising winter temperatures associated with climate warming has been an area of particular interest in boreal and temperate regions where a period of cool temperatures in fall and winter is required to break plant dormancy. In this study, we examined the budburst and growth of trembling aspen (Populus tremuloides Michx.), balsam poplar (Populus balsamifera L.), white birch (Betula papyrifera Marsh.), black spruce (Picea mariana (Mill.) B.S.P.), white spruce (Picea glauca (Moench) Voss), jack pine (Pinus banksiana Lamb.), and lodgepole pine (Pinus contorta Dougl. ex. Loud.) seedlings subjected to typical northern Ontario, Canada, spring conditions in climate chambers after different exposures to natural chilling. Results indicate that chilling requirements (cumulative weighted chilling hours) differed substantially among the 7 species, ranging from 300 to 500 hours for spruce seedlings to more than 1100 hours for trembling aspen and lodgepole pine. Only spruce seedlings had fulfilled their chilling requirements before December 31 whereas the other species continued chilling well into March and April. Species with lower chilling requirements needed more heat accumulation for budburst and vice versa. Insufficient chilling delayed budburst but only extremely restricted chilling hours (<400) resulted in abnormal budburst and growth, including reduced needle and shoot expansion early budburst in lower crowns, and erratic budburst on lower stems and roots. Effects, however, depended on both the species’ chilling requirements and the chilling–heat relationship. Among the 7 tree species examined, trembling aspen is most likely to be affected by reduced chilling accumulation possible under future climate scenarios, followed by balsam poplar, white birch, lodgepole pine, and jack pine. Black and white spruce are least likely to be affected by changes in chilling hours.